(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This research was conducted to determine the influence of physico-chemical characteristics on diversity of the intermediate host of schistosomes in Makwaye and Kubanni reservoirs, Zaria, Nigeria. Materials and methods: Physico-chemical characteristics and diversity of the intermediate host of schistosomes in Makwaye and Kubanni reservoirs, Zaria, Nigeria, were investigated for a 12-month period (January to December, 2014). Physico-chemical properties were analyzed according to the standard procedures for examination of water and waste waters. The molluscs were collected using an Ekman grab model number 923, measuring 19 cm by 14 cm with an area of 0.0266 m2. PAST software was used to run Principal Component Analysis, Shanon-Weiner diversity index and Cluster analysis. Results: A total of 978 Bulinus globosus and 3612 Biomphalaria pfefferi were recorded in Makwaye reservoir with high abundance in dry season while a total of 163 B. globosus and 602 B. pfefferi was recorded in Kubanni reservoir with higher abundance in wet season. Shanon-Weiner diversity index of Makwaye reservoir also ranged from 2.01-2.22 and 1.16-1.31 in Kubanni reservoir. Significant variations (P≤0.05) were observed in physicochemical parameters, schistosomes intermediate host abundance with seasons. Principal Component Analysis (PCA) revealed significant influence (P≤0.05) of physicochemical properties on schistosome intermediate host composition, with BOD, DO, pH and Calcium significantly influencing the presence of B. globosus and B. pfefferi in both reservoirs. Conclusion: It is concluded that the presence of these molluscs in the study areas may constitute a predisposing factor to schistosomiasis and therefore, various management strategies and recommend preventive measures to people coming in contact with these two reservoirs. ht//doi.org/10.5455/javar.2017.d235tp: